Preparation and characterization of electrospun polylactic acid/sodium alginate/orange oyster shell composite nanofiber for biomedical application - BİLĞİÇ ALKAYA, DİLEK; OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; KILIÇ, OSMAN; AYAZ SEYHAN, SERAP (SPRINGER, 2020)
Bone tissue engineering has begun to draw attention in recent years. The interactive combination of biomaterials and cells is part of bone tissue engineering. Sodium alginate (SA) is a biologically compatible, degradable, non-toxic natural polymer accepted by the human body and is widely used in the field of tissue engineering. Polylactic acid (PLA) is another type of biodegradable thermoplastic polyester derived from renewable sources which are used in bone tissue engineering and biomedical owing to its biocompatibility and biodegradability. Hydroxyapatite (HA) and tricalcium phosphate (TCP) derived from natural sources such as marine species and bovine bone are biocompatible and non-toxic biomaterials which are used to reconstruct many parts of the skeleton. In this study, PLA, SA with different compositions, and nanofibers obtained by adding orange spiny oyster shell powders (Spondylus barbatus) to them by using electrospining technique. Cell culture study, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and physical analysis such as density, electrical conductivity, surface tension, viscosity measurement, and tensile strength measurement tests were carried out after the production process. Produced nanofibers showed smooth and beadless surface. The average diameters and distributions decreased with the addition of optimum PLA and TCP amount. The tensile strength of nanofibers was enhanced with the additional SA and TCP. The produced nanofibers are compatible with human bone tissue, which are not cytotoxic, and in addition, a high cell efficiency of SaOS-2 cells on the nanofibers was observed with SEM images.
Keywords: Electrospinning; Nanofibers; Polylactic acid; Sodium alginate; Bone tissue engineering; Biomaterials; NANOCOMPOSITE SCAFFOLDS; POWDER PRODUCTION; L-LACTIDE; TISSUE; PHOSPHATE; BIOCOMPATIBILITY; ANTIBACTERIAL; BIOMATERIALS; FABRICATION; MORPHOLOGY